2021
DOI: 10.33448/rsd-v10i13.21130
|View full text |Cite
|
Sign up to set email alerts
|

Leaves of Olea europaea L. as a source of oleuropein: characteristics and biological aspects

Abstract: Olive fruits, leaves and derived virgin oils are known to be good sources of polyphenols and other antioxidants that have recently received increasing interest. In addition, its derivatives are responsible for the bitter and spicy taste of green olive fruits and virgin olive oils. In the physiology of the olive plant, the enzymatic biotransformation of oleuropein is related to fruit ripening and the tissue-specific defense mechanism. The oleuropein is one of the main phenolic compounds identified in fruits and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 92 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…Numerous previous studies have shown that olive leaf extract (OLE) is a rich source of various phenolic compounds with numerous health-protective properties (i.e., antioxidant, anticarcinogenic, anti-inflammatory, antihypertensive, cholesterol-lowering, etc. ), of which oleuropein was found in the highest concentrations (up to 14%) [10,[12][13][14][15][16]. The European Food Safety Agency (EFSA) has recognised the beneficial effects of OLE on human health, paving the way for the potential use of OLE to supplement foods to prevent various diseases and maintain human health [17].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous previous studies have shown that olive leaf extract (OLE) is a rich source of various phenolic compounds with numerous health-protective properties (i.e., antioxidant, anticarcinogenic, anti-inflammatory, antihypertensive, cholesterol-lowering, etc. ), of which oleuropein was found in the highest concentrations (up to 14%) [10,[12][13][14][15][16]. The European Food Safety Agency (EFSA) has recognised the beneficial effects of OLE on human health, paving the way for the potential use of OLE to supplement foods to prevent various diseases and maintain human health [17].…”
Section: Introductionmentioning
confidence: 99%